First serological evidence of West Nile virus infection in wild birds in Northern Algeria. (April 2020) - Medrouh, Bachir; Lafri, Ismail; Beck, Cécile; Leulmi, Hamza; Akkou, Madjid; Abbad, Lynda; Lafri, Mohamed; Bitam, Idir; Lecollinet, Sylvie
Abstract: While the epidemiology of Flaviviruses has been extensively studied in most of the Mediterranean basin, little is known about the current situation in Algeria. In order to detect the circulation of West Nile (WNV) and Usutu viruses (USUV) in Kabylia, 165 sera were collected from two wild birds species, namely the long distance migrant Turdus philomelos (song thrush) (n = 92) and the resident Passer domesticus (house sparrow) (n = 73). A total of 154 sera were first analyzed by commercial competition ELISA. WNV and USUV micro-neutralization tests were performed on all c-ELISA positive sera and all samples with poor volume. Overall, 7.8 % (CI95 %: 3.5–11.9) were positive by c-ELISA. Positive results were detected in 12.5 % (CI95 %:5.6–19.4) of song thrushes and 1.5 % (CI95 %: 0.0–4.5) for sparrow. Micro-neutralization tests revealed an overall seroprevalence of 6.7 % for WNV (CI95 %: 2.9–10.3), Neutralizing antibodies were found in 8.7 % (CI95 %: 3.0–14.4) for song thrushes and in 4.1 % (CI95 %: 0.0–8.7) of sparrows. The current study demonstrates significant seroprevalence of WNV antibodies in wild birds in Algeria.